Vaccinations—Between free will and coercion - Patryn, Rafał K. (Hum Vaccin Immunother, 2016)
Dynamically changing social situation associated with migrations, increasing freedom rights, popularity of anti-vaccine movements and the resulting from that decrease in herd immunity, forces the medical society and the governments of various countries to reflect on the attitude toward vaccinations. Issues of freedoms and self-determination frequently do not accept any medical coercion in case of prophylactic vaccinations, however, recent waves of epidemics revealed that there is a necessity for undertaking strict legal actions to encourage vaccinations. After analyzing various legal approaches toward vaccinations we believe that personal coercion in case of vaccination refusal has too far reaching sanctions and propose the possibility of balancing the right to autonomy and the medical coercion. We postulate that vaccination refusal should be equivalent with covering frequently high medical costs in case of infection, The threat of financing medical treatment should influence the decision making process of those opposing vaccinations simultaneously respecting their rights not too get vaccinated.